The difference between the two functions is:
[tex](f - g)(x) = -x^2 - 9x + 8[/tex]
Here we have:
[tex]f(x) = -x^2 - 8x + 7\\\\g(x) = x - 1[/tex]
And we want to find (f - g)(x), which is equal to f(x) - g(x), then we can write:
[tex](f - g)(x) = (-x^2 - 8x + 7) - (x - 1) = -x^2 -8x + 7 - x + 1 = -x^2 - 9x + 8[/tex]
So we conclude that the difference between the two functions is:
[tex](f - g)(x) = -x^2 - 9x + 8[/tex]
If you want to learn more about functions:
https://brainly.com/question/2456547
#SPJ1